Persepsi Mahasiswa terhadap Implementasi Pendekatan Keterampilan Proses dalam Matakuliah Pembelajaran IPS SD - Rusmawan Rusmawan; Andreas Erwin Prasetya (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
Social Studies learning will be meaningful if it involves students. One effort is by implementing process skills-based learning. The purpose of this study is to describe students' perceptions of the implementation of process skills in the Social Studies learning course. This research is qualitative descriptive research. The research subjects consisted of 70 students participating in the Social Studies Learning course in the PGSD Study Program at Sanata Dharma University. The objects of this study include students' perceptions of interesting aspects, challenges, thinking abilities, and social interactions in the stages of process skills in Social Studies learning. The research instrument consisted of an open questionnaire. Data were analyzed qualitatively. The results of the study: (1) students tend to enjoy the stage of observing phenomena and presenting results in Social Studies learning with process skills the most, (2) the stages of processing data and formulating questions are often considered the most difficult parts, (3) drawing conclusions is considered the most mentally draining part because students have to synthesize all the data, and (4) the implementation of process skills in social studies learning in lectures makes students feel more sensitive to social issues. The implication of this research is that social studies learning lectures with a process skills approach effectively improve academic ability and social interaction, but special attention is needed in the stages of data analysis, question formulation, and conclusion drawing in social studies learning courses so that it does not become an excessive burden for students.